Pengembangan Lembar Kerja Peserta Didik Berbasis Kearifan Lokal Sumatera Selatan Pelajaran Seni Budaya dan Prakarya di Sekolah Dasar - Pravitasari, Dyah; Septikasari, Resti; Rohmah, Mushlihah; Rohmah Siregar, Siti (Jurnal Riset Madrasah Ibtidaiyah, 2025)
This study aims to develop a Student Worksheet (LKPD) based on the local wisdom of South Sumatra for the Seni Budaya dan Prakarya (SBdP) subject at the elementary school level. The development was carried out using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included observation, interviews, documentation, and validation questionnaires, while data analysis focused on media feasibility, content quality, and student responses to the LKPD implementation. The results showed that the local wisdom-based LKPD met expert validity standards for content (84.57%) and media (84.7%), was rated highly practical based on students' positive responses, and effectively improved their understanding of local cultural values. This LKPD was designed not only as a learning tool but also as a means of internalizing regional culture. Through a contextual, engaging, and value-rich approach, students are encouraged to recognize, appreciate, and preserve the cultural heritage of South Sumatra. The LKPD holds potential for fostering character education and strengthening national cultural identity from an early age.